Microbes as tools for cell biology - Russell, David G., 1956- (Methods in cell biology, 1994)
Microbes as Tools for Cell Biology bridges the gap between cell biology and microbiology. This laboratory guide provides a microbial tool kit for biologists who wish to use microbes as probes for basic cellular functions. The volume is organized into three sections, covering essential information on culture and genetic manipulation of microbes, assays for pathogen-host recognition, and analysis of intracellular parasitism. Each chapter outlines practical procedures and describes the rationale behind their development. This volume should prove useful to anyone interested in the biology of infectious agents, or their exploitation as a new generation of cell biological reagents. Key Features * Introduction by renowned microbiologist Dr. Stanley Falkow * Covers manipulation of pathogens, especially generation and selection of non-virulent phenotypes * Guides researchers in the study of intracellular pathogenesis * Describes microbial adherence and phagocytosis assays * Focuses on protein trafficking in infected cells * Well-illustrated with color plates, halftones, and diagrams.